Efficacy of the 26-Kilodalton Outer Membrane Protein and Two P5 Fimbrin-Derived Immunogens To Induce Clearance of Nontypeable Haemophilus influenzae from the Rat Middle Ear and Lungs as Well as from the Chinchilla Middle Ear and Nasopharynx - Kyd, Jennelle M. (American Society for Microbiology, 2003)
The rat middle ear and lung clearance model has been used to show that the nontypeable Haemophilus influenzae 26-kDa outer membrane protein OMP26 is highly efficacious as a mucosal immunogen, inducing significantly enhanced clearance in immunized rats upon direct challenge of these two anatomic sites. Similarly, the chinchilla model of middle ear and nasopharyngeal clearance has been used to show that two P5 fimbrin adhesin-derived immunogens, LB1 and lipoprotein D (LPD)-LB1(f)(2,1,3), are highly efficacious as parenteral immunogens. Both induced significantly augmented clearance of nontypeable H. influenzae upon challenge of these sites. Here, these three nontypeable H. influenzae immunogens in addition to six bovine serum albumin and keyhole limpet hemocyanin conjugates of the synthetic peptide LB1(f) were assayed for relative efficacy in the reciprocal rodent model system. OMP26 was assayed in the chinchilla host by a parenteral immunization route, with clearance of the middle ear and nasopharynx used as outcome measures. Both LB1 and LPD-LB1(f)(2,1,3) were assayed in the rat host with a mucosal immunization route and clearance of nontypeable H. influenzae from the lungs and middle ears as outcome measures. Both of the immunogens were found to induce a high-titered and specific immune responses in the heterologous host system. Moreover, each was found to be highly efficacious in the reciprocal host system, providing strong support for the continued development and inclusion of both OMP26 and P5 fimbrin-derived peptides as candidate vaccine antigens directed at otitis media caused by nontypeable H. influenzae.